Suppressing scratch-induced brittle fracture in silicon by geometric design modification of the abrasive grits - Kovalchenko, Andrii M.; Goel, Saurav; Zakiev, Islam M.; Pashchenko, Evgeniy A.; Al-Sayegh, Rajab (Elsevier, 2018)
The overarching goal of this research was to investigate the application of spherically shaped abrasive particles in achieving ductile-mode cutting. Scratching experiments were carried out to assess the differences between arbitrarily and spherically shaped diamond and tungsten carbide (WC) grits in inducing brittle fracture or ductile plasticity in single-crystal silicon. It was observed that the arbitrarily shaped particles produce brittle fracture in contrast to the spherically shaped grits. The sharp edges and corners of grits result in high tensile stress-concentrated regions causing cracking and spalling. Contrary to this, spherically shaped WC particles induce uniform cutting pressure, which suppresses the extent of the brittle fracture and the mode of material removal was completely dominated by ductile-cutting until a threshold load for ductile-to-brittle transition (the first cracks appearance). These observations are expected to provide a suitable pathway in making the Diamond Wire Sawing machining operations more robust by providing a control on brittle damage.
Keywords: Silicon; Diamond; Tungsten carbide; Ductile mode cutting; Scratching; Diamond wire sawing machine operations